(untitled) (Economy of Regions, 2025)
Erratum: Pletnev,D.A., Lipina, E.V., & Naumova, K. A. (2024). Regional Features of Russian Gazelles During the Pandemic. Ekonomika regiona / Economy of regions, 20(3), 686-701. https://doi.org/10.17059/ekon.reg.2024-3-6 On the pages 686 and 687 there were mistakes in the affiliation of Dmitry Pletnev in Russian and in English, accordingly. The correct affiliation is: Д. А. Плетнев а), Е. В. Липина б), К. А. Наумова в) а) Челябинский филиал Института экономики УрО РАН, г. Челябинск, Российская Федерация б, в) Челябинский государственный университет, г. Челябинск, Российская Федерация Dmitri A. Pletnev a), Elena V. Kozlova b), Kseniia A. Naumova c) a) Chelyabinsk Branch of the Institute of Economics of UB RAS, Chelyabinsk, Russian Federation b, c) Chelyabinsk State University, Chelyabinsk, Russian Federation.